Implementasi Program Pencegahan Dan Pemberantasan Penyalahgunaan Dan Peredaran Gelap Narkoba (P4GN) Oleh Badan Narkotika Nasional (BNN) Kabupaten Tulungagung Sebagai Bentuk Edukasi Formal Dalam Mengurangi Penyalahgunaan Narkoba Di Kalangan Pelajar - Novitasari, Erika (Sekolah Tingi Keguruan dan Ilmu Pendidikan (STKIP) PGRI Tulungagung, 2018)
One This study aims to determine the implementation of the program Prevention and Eradication Abuse and Illicit Circulation of Drugs (P4GN) by the National Narcotics Agency (BNN) Tulungagung District as a form of formal education in reducing drug abuse among students. Location in this research is at office of National Narcotics Agency (BNN) of Tulungagung Regency. In this research the researcher use descriptive qualitative method. Respondents in this research are Kagab prevention field, Head of rehabilitation field, teacher Bimbingsn Counseling and students enrolled in drug rehabilitation participant in National Narcotics Agency (BNN) of Tulungagung Regency. Tekin data collection is by obserasi, interview and study documentation. In the data analysis the researcher uses 3 stages of data reduction, data presentation and mengabil conclusion and verification. The results of this study found that in the implementation of the program Prevention and Eradication Abuse and Illicit Circulation of Drugs (P4GN) by the National Narcotics Agency (BNN) Tulungagung District as a form of formal education in reducing drug abuse among students, that is in the implementation at school is already running, though not fully done with the maximum. So that there needs to be a regular evaluation and regular, in order to fully suppress the number of drug abuse among students